CHEMICAL AND FATTY ACID COMPOSITION OF POULTRY MEAT AND PORK FATBACK AS A RAW MATERIAL FOR THE PRODUCTION OF FRANKFURTERS - Daniela Belichovska, Zlatko Pejkovski, Aleksandra Silovska Nikolova, Katerina Belichovska, Rodne Nastova, Natasha Gjorgovska (Macedonian Journal of Animal Science, 2020)
The aim of the present research was to investigate the chemical composition and fatty acid profile of poultry meat and pork fatback, which were used as a raw material for the production of frankfurters. Skinless, boneless chicken meat (breast and drumstick) cleaned from adipose and connective tissue was used in the examinations, as well as pork fatback, which are the most common raw material for production of sausages. pH value, chemical composition (water, protein, fat and ash), cholesterol and fatty acid content were determined in chicken meat and pork fatback. Drumstick showed higher pH (6.48) than breast (5.92) and pork fatback (5.99) and contained more cholesterol (70.08 mg/100 g vs. 65.64 and 65.33 mg/100 g). Breast contained more protein (23.90%) than drumstick (19.86%) and less fat (1.88% vs. 7.24%). Pork fatback contained 13.79% water, 3.45% protein, 82.65% fat. The most common fatty acids in chicken meat were linoleic, oleic and palmitic. Drumstick contained more linoleic (30.40%) and oleic acid (28.38%) than breast (26.52% and 23.88%) and less palmitic acid (21.49% vs. 25.20%). Breast were richer in arachi-donic, docosahexaenoic and docosapentaenoic acid. Drumstick contained more monounsaturated (MUFA) and polyunsaturated (PUFA) and less saturated (SFA) fatty acids. The ratio PUFA/SFA was higher in drumstick and n-6/n-3 ratio was very close to that of breast. The most common fatty acids in pork fatback were oleic (34.19%), palmitic (26.55%), stearic (14.84%) and linoleic (13.34%).
Keywords: chicken meat; pork fatback; chemical and fatty acid composition